Emotional Intelligence and Self Efficacy as A Contributor of Student Mathematics Learning Outcomes - Ibrahim Ibrahim (Universitas Negeri Padang, 2022)
This study aims to determine the contribution of emotional intelligence and self-efficacy to mathematics learning outcomes with the research object of 52 grade IX students in the 2020/2021 school year of MTsN 1 Yogyakarta. This type of research is quantitative with ex post facto research methods. The instrument used is a scale of emotional intelligence and self-efficacy. The data analysis technique used is multiple regression analysis. The results of data analysis show that the value of R = 0.479 and R2 = 0.229 with the probability value in the regression test being 0.002. These results mean that emotional intelligence and self-efficacy contribute to students' mathematics learning outcomes